A new record of Pontobdella muricata (Annelida: Hirudinea: Piscicolidae) from Iskenderun Bay, northeastern Mediterranean Turkey - Yanar, Alper; Özak, Argun Akif; Başusta, Nuri (Universitatea din Oradea, 2019)
The aim of this study is to report a new record of marine leech, Pontobdella muricata (Linnaeus, 1758) from Iskenderun Bay, northeastern Mediterranean. Fish samples were collected during a trawl fishing conducted at a depth ranging from 150 to 300 m in Iskenderun Bay, Turkey. Fish samples, infected with marine leech, was transferred to the ecophysiology laboratory in Fisheries Faculty of the Firat University. One infected fish was photographed and the parasite was removed from the host and fixed in ethanol for further morphological examinations and measurements. The parasite was identified as Pontobdella muricata. Dipturus oxyrinchus constitutes new host for Pontobdella muricata which is one of the most common species of leeches found on skates and rays. ©Biharean Biologist, Oradea, Romania, 2019
Keywords: Dipturus oxyrinchus; Hirudinea; Mediterranean; Parasite; Pontobdella muricata